PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT.PRESOL INDO PRIMA PALEMBANG - Irawan, Benny (MOTIVASI, 2016)
Purpose - The purpose of this research was to determine the effect of the Competence and Working Environment influence on employee performance. Design/methodology - Respondents in this study were allemployees of PT . Presol Indo Prima Palembang branch of which there are 39 employees. Samples were taken using census where the entire population isused as a sample in research and data collection tools used questionnaire analysis method used is multiple linear regression with SPSS 17.0. Findings – The author finds that the results of testing with T test and F test that accepted meaning Competence and Working environment influence significant effect on employee performance